2011
DOI: 10.1111/j.1365-2400.2010.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional trends of fisheries in the River Ganges, India

Abstract: Monthly surveys of local fisheries from five principal landing sites on the River Ganges at Bhagalpur, India, were conducted from 2001 to 2007. Fishes of a range of sizes with mostly periodic-type life-history strategies, including many catfishes and carps, dominated the catch. Average annual yield (total mean monthly catch in units of biomass) was highly variable but trended downward during the study. Statistical ordination revealed associations between assemblage composition and hydrological seasons. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…In general, information on spawning season, reproductive strategies, habitat associations and other ecological data from LEK matched closely with published literature on freshwater fish life histories (Montana et al, ; Qasim & Qayyum, ; Talwar & Jhingran, ; Vass, Mondal, Samanta, Suresh, & Katiha, ; Vass, Tyagi, Singh, & Pathak, ; Welcomme, Winemiller, & Cowx, ; Winemiller, ; Zeug & Winemiller, ). This information was used to find explanations for causes of declines fishers attributed to different species.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In general, information on spawning season, reproductive strategies, habitat associations and other ecological data from LEK matched closely with published literature on freshwater fish life histories (Montana et al, ; Qasim & Qayyum, ; Talwar & Jhingran, ; Vass, Mondal, Samanta, Suresh, & Katiha, ; Vass, Tyagi, Singh, & Pathak, ; Welcomme, Winemiller, & Cowx, ; Winemiller, ; Zeug & Winemiller, ). This information was used to find explanations for causes of declines fishers attributed to different species.…”
Section: Resultssupporting
confidence: 77%
“…An adverse outcome of conflicts has been distress-induced labour migration of fishers to distant regions, many having by now permanently exited the dangerous setting (Kelkar, 2018). The department's association with fishers has existed since 1999 through long-term fisheries monitoring and research conducted in conservation programmes for endangered Ganges river dolphins and other biodiversity (Choudhary et al, 2015;Choudhary, Smith, Dey, Dey, & Prakash, 2006;Montana, Choudhary, Dey, & Winemiller, 2011). Documenting long-term F I G U R E 1 Map showing locations of fishing settlements in the Bhagalpur district, Bihar, India, from which local ecological knowledge (LEK) data were compiled for our study [Colour figure can be viewed at wileyonlinelibrary.com] insights from local ecological knowledge (LEK) is thus important to place environmental and social change in perspective, for the management of fisheries in the Ganga river-floodplain ecosystem.…”
Section: Study Area and Historical Contextmentioning
confidence: 99%
“…This shower slightly increasing trend and 2006 and 2007 pH level from 7.3 to 7.5 was quite stable. In the present study, the pH tended to be higher than those reported by Montana (2011), which was suitable for breeding and nursery of hilsa. Overall, the environmental variables in the present study was found to be consistent with those reported by several researchers (Sharif 2017a, b;Montana 2011;Ahsan 2014).…”
Section: Variations In Cpue Of Hilsa At Different Habitats Of Bangladeshcontrasting
confidence: 54%
“…70 -8.30 and 7.9 -8.40 for breeding and nursery activities, respectively, while the salinity was <0.1 ppt. Montana (2011) found the pH level of 6.5 in 2003 summer to 7.5 in summer, monsoon and winter at the River Ganges at Bhagalpur, India. This shower slightly increasing trend and 2006 and 2007 pH level from 7.3 to 7.5 was quite stable.…”
Section: Variations In Cpue Of Hilsa At Different Habitats Of Bangladeshmentioning
confidence: 93%
“…The range of ammonia, nitrate, phosphate, TSS, temperature and DO readings were considered high throughout the study period. According to Montana et al (2011) and Singh (2007), this phenomenon happened due to seasonal response to watershed geology, topography, vegetation and hydrology. As observed in our study, during the rainy season, for example for TSS, the range was very high because of the high concentration of sediments carried by the river.…”
Section: Discussionmentioning
confidence: 99%